Psychische Komorbidität in der Intensivmedizin - Niecke, Alexander; von Bassewitz, Valeska Gräfin; Michels, Guido (DMW - Deutsche Medizinische Wochenschrift, 2019)
This article aims to provide an overview of the nature and extent, risk factors and treatment strategies of co-morbid mental disorders in the context of intensive care medicine. Depressive, anxious and posttraumatic syndromes as well as deliria are common phenomena in critical care patients, which correspond with the course and outcome of the underlying physical illness. The most important factors for the occurrence of mental comorbidity and general principles of care are described.
Keywords: psychische Störungen; Intensivmedizin; Prävalenz; Risikofaktoren; psychosoziale Versorgung